Analisis Komposisi Bahan Bakar Terhadap Proses Pembakaran pada Kompor Berbahan Bakar Oli Bekas - Mubin, Moh. Nurul; Riandadari, Dyah; Wulandari, Diah; Nugroho, Aji (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Waste management issues have become a national concern with serious impacts on social, economic, health, and environmental aspects. The low level of awareness among communities and industrial actors in managing waste has contributed to environmental pollution. Along with the development of cities and regions, the volume of waste including used lubricating oil from vehicles and motorized machinery continues to increase. Not only in large cities, but small workshops in rural areas also generate used oil waste, resulting in its widespread distribution across Indonesia. This study employed a field experimental method. The approach was conducted by testing fuel mixture compositions in a stove fueled by used oil to observe the effect of fuel composition on the combustion process. The results indicate that variations in fuel composition significantly affect combustion quality. In the mixture of used oil and kerosene, a ratio of 40:60 produced the highest flame temperature of 378°C, the fastest cooking time of 4.05 minutes, and a blue flame indicating more optimal combustion. In contrast, the 60:40 mixture resulted in the lowest temperature of 318°C, the longest cooking time of 5.07 minutes, and a predominantly orange flame. For the mixture of used oil and biodiesel (biosolar), the 40:60 ratio also demonstrated the best performance, achieving the highest flame temperature of 380°C, the fastest cooking time of 3.52 minutes, and a stable blue flame.